Modelling the Spreading Pattern and Prevention Strategies of COVID-19 in Nigeria - Olabode, Abiodun Daniel; Musa, Ibrahim Zakariyya; Sabo, Shamsuddeen Ahmad; Sambo, Muhammad Bello (International Journal of Computer Sciences and Engineering, 2020)
It is obvious that the World right now is in the stagnant position due to COVID-19. The problem of this pandemic is its mode of transmission from person to person on daily basis. This study aims at modelling the spreading pattern of the disease in Nigeria with a view to understanding how the spread can be curbed. Secondary data collected from Nigerian Center for Disease Control (NCDC) between 29th Feb 2020 and 30th May 2020 were used. These daily data were further grouped into 14 weekly data. Parameters like number of suspected persons, the number of people quarantined and the total number of active cases were used to develop the model thus; the undetected infected people were termed as Hidden nodes ( ) defined as , where: is the suspected case of period and is the number of infected people that were isolated in period . Each undetected infected person (hidden node) can infect several people in a given time (day, week or month), also those infected that show symptoms will also be fished out, tested and isolated if they were positive will be recorded as . This model has established the maximum number of days to be spent in a lockdown period, given a certain number of confirmed cases to control the spread of the disease.